Evaluation of the chemical composition and antimicrobial effect of Thuja essential oil - Eugenia Dumitrescu, Mihai Folescu, Cristina T. Romeo (Medicamentul Veterinar)
Starting from the consideration that the pharmacological and therapeutic properties of an essential oil are given by their chemical components, components that differ depending on the origin, soil, temperature, humidity, etc., we set out to determine the content of volatile compounds in the oil essential thuja purchased from the trade and to test its antimicrobial effect. The objectives of the research were to identify volatile compounds from thuja essential oil by the GS-MS method and to test the antimicrobial effect on gram positive and gram negative species. The obtained results showed that Thuja essential oil has significant inhibitory effects against gram-positive and gram-negative bacteria, which are associated with clinical diseases; it is more effective against gram positives than gram negatives; ineffective against Salmonella typhimurium and the major components identified were: α-pinene, 3-carene, terpinolene, limonene, β-myrcene and camphene. The presence of these compounds shows that thuja essential oil has a great potential for use in many medical applications.